Visual processing of actions directed towards three-dimensional objects in immersive virtual reality may involve holistic processing of object shape - Juliano, Julia M.; Phanord, Coralie S.; Liew, Sook-Lei (Frontiers in Virtual Reality, 2022)
Immersive virtual reality using a head-mounted display (HMD-VR) is increasing in use for motor learning and motor skill training. However, it remains unclear how visual information for action is processed in an HMD-VR environment. In the real world, actions towards three-dimensional (3D) objects are processed analytically and are immune to perceptual effects, such as processing object dimensions irrelevant to performing the action (i.e., holistic processing). However, actions towards two-dimensional (2D) objects are processed holistically and are susceptible to perceptual effects. In HMD-VR, distances are often underestimated, and the environment can appear flatter compared to the real world. Thus, actions towards virtual 3D objects in HMD-VR may be processed more like 2D objects and involve holistic processing, which is susceptible to perceptual effects. In an initial study, we used a Garner interference task to examine whether vision-for-action in HMD-VR is processed holistically and hypothesized that vision-for-action towards virtual 3D objects in HMD-VR would result in a Garner interference effect, suggesting holistic processing. We found Garner interference effects for reaction times to reach maximum grip aperture and to complete movement. These results show that visual processing of actions towards virtual 3D objects in HMD-VR may involve holistic processing of object shape. These findings demonstrate that visual information for action in HMD-VR is processed differently compared to real 3D objects and is susceptible to perceptual effects, which could affect motor skill training in HMD-VR.